ENVIRONMENTAL TAXATION POLICY: THE CASE OF TAXES ON MOTOR FUELS IN THE EUROPEAN UNION - Kaplanović, Snežana M.; Manojlović, Aleksandar V. (Journal of Applied Engineering Science, 2013)
The first part of the paper researches and states the reasons why tax on motor fuels is considered one of the most important economic instruments in transport sector. In addition, the paper presents possible ways of differentiating motor fuels taxes and analyses the justification for imposing such taxes from the ecological viewpoint. The second part of the paper devotes special attention to the analysis of this economic instrument’s application in the European Union Member States, as well as its place and role in the environmental protection policy.